Childhood abuse and association with adult depressive symptoms among people with cardiovascular disease - Yin, Ruoyun; Yang, Yuan; Tang, Lei; Chang, Yujiao; Zhang, Fan (Frontiers in Public Health, 2023)
Backgroud: To study the association between the total / different types of childhood abuse and adult depressive symptoms in people with CVD. Methods: The subjects were people with CVD who continuously participated in the China Health and Retirement Longitudinal Study(CHARLS) life history survey and the 2018 wave of the CHARLS national baseline Survey. Multi-level logistic regression models were used to analyze the relationship between emotional neglect, physical neglect, physical abuse and adult depressive symptoms. Results: A total of 4823 respondents were included in this study. The incidence of childhood abuse was 43.58% among people over 45 years old with CVD, which was higher than that of the general population (36.62%, p<0.05). Adjusted model showed that overall childhood abuse was associated with adult depressive symptoms (OR=1.230, 95%CI:1.094-1.383). Among different types of childhood abuse, only physical abuse was associated with depressive symptoms in adulthood (OR=1.345, 95%CI:1.184-1.528). Conclusions: Compared with the general elderly population, the incidence of childhood abuse in CVD population is higher. Physical abuse in childhood increases the risk of depressive symptoms in adulthood. In order to reduce the occurrence of adult depression, it is worth considering childhood abuse.